Effects of the Computer Desk Level on the Musculoskeletal Discomfort of Neck and Upper Extremities and EMG Activities in Patients with Spinal Cord Injuries - Bo-Ra Kang; Jin-Gang Her; Ju-Sang Lee; Tae-Sung Ko; Young-Youl You (Hindawi-Wiley, 2019)
Background. Computers are used as a means of social communication, for work and other purposes. However, patients with spinal cord injuries may have a higher risk than normal individuals with musculoskeletal problems when using computers owing to their inability to control respective postures due to problems in motor and sensory functioning. Objectives. This study is aimed at identifying the effect of computer desk heights on musculoskeletal discomforts of the neck and upper extremities and EMG activities in patients with spinal cord (C6) and upper thoracic spinal cord injuries. Methods. Participants of the present study were the patients diagnosed with ASIA A or B. The patients were divided into two groups according to their spinal cord injuries: C6 group and T2-T6 group. The level of the desk was set at 5 cm below the elbow, at the elbow level, and 5 cm above the elbow level. Electromyography was used to measure the duration of typing task EMG(%RVC) of the cervical erector spinae, upper trapezius, anterior deltoid, and wrist extensor. Subjective musculoskeletal discomfort (Borg-RPE) was measured at the end of the experiment. Results. The two groups showed differences in terms of RPE corresponding to each level of the computer desk (p<.05). Postanalysis revealed the C6 group had decreased RPE as the level of computer desk increased, whereas the subjects in the T2-T6 group had decreased RPE values in accordance with the decreasing level of computer desk (p<.05). In EMG, both groups had no significant differences (p>.05). However, in terms of the interaction between the muscles and the level of computer desk in both groups, the differences in the interactions of the upper trapezius and wrist extensor with each level of the desk were found (p<.05). Conclusion. This study is meaningful in that it confirms computer work posture and preference of spinal cord-injured individuals.